Measurements of fiducial cross-sections for tt[bar] production with one or two additional b-jets in pp collisions at √s = 8 TeV using the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (The European physical journal. C, Particles and fields, 2016)
Fiducial cross-sections for tt¯ production with one or two additional b-jets are reported, using an integrated luminosity of 20.3 fb−1 of proton–proton collisions at a centre-of-mass energy of 8 TeV at the Large Hadron Collider, collected with the ATLAS detector. The cross-section times branching ratio for tt¯ events with at least one additional b-jet is measured to be 950 ± 70 (stat.) +240−190 (syst.) fb in the lepton-plus-jets channel and 50 ± 10 (stat.) +15−10 (syst.) fb in the eμ channel. The cross-section times branching ratio for events with at least two additional b-jets is measured to be 19.3 ± 3.5 (stat.) ± 5.7 (syst.) fb in the dilepton channel (eμ, μμ, and ee) using a method based on tight selection criteria, and 13.5 ± 3.3 (stat.) ± 3.6 (syst.) fb using a looser selection that allows the background normalisation to be extracted from data. The latter method also measures a value of 1.30 ± 0.33 (stat.) ± 0.28 (syst.)% for the ratio of tt¯ production with two additional b-jets to tt¯ production with any two additional jets. All measurements are in good agreement with recent theory predictions.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, M. Wessels [und sehr viele weitere Personen]
Im Titel steht der Buchstabe t mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 17.06.2020